Effects of saffron-grape intercropping on saffron flower number and rhizosphere microbial community - Yuanyuan Tao; Guifen Zhou; Xingchang Zhang; Mengqing Feng; Liqin Li; Xiaodong Qian (BMC Microbiology)
Abstract Background Saffron (Crocus sativus L.) is a valuable herb. With the increasing demand for saffron, people are starting to focus on how to increase its yields. Intercropping and microbial interactions have a positive effect on plant yield, including enhanced soil fertility, enriched microbial diversity, reduced pest and disease incidences, and improved plant growth. However, the impact of intercropping saffron with other plants on saffron yields and soil microbial community diversity remains unclear. In our study, we counted the number of saffron flowers in two cropping patterns (saffron monoculture and saffron-grape intercropping), and analyzed the microbial community diversity and composition using Illumina high-throughput sequencing methods based on 16 S and ITS amplicons. Results The results showed that saffron-grape intercropping significantly increased number of flowers compared to saffron monoculture (P < 0.01). Saffron-grape intercropping influenced rhizosphere soil chemical properties and altered rhizosphere microbial communities. The pH of intercropped rhizosphere soil increased significantly from 5.84 to 6.43. Spearman’s correlation revealed a significantly positive correlation between pH and Bacillus, Sphingomonas, Sphingobacterium, Halomonas, Pseudolabrys, and Dongia. Conversely, it showed a significant negative correlation with Pedobacter, Achromobacter, Tumebacillus, and Sphingopyxis in bacteria. In fungi, a significant negative correlation was observed. Although there was no significant difference in diversity, intercropping increased the observed richness and biodiversity of both bacteria and fungi compared to monoculture. The intercropping led to a higher relative abundance of bacterial genera such as Sphingomonas and Streptomyces, as well as fungal genera including Acremonium, Llyonectria, Penicillium, Cadophora, Plectosphaerella, and Tetracladium. Intercropping decreased the dominance of certain microbial taxa, including Fictibacillus, Microbacterium, and Glutamicibacter among bacterial genera, as well as Fusarium and Arthrographis among fungal genera. Additionally, functional analysis revealed that intercropping was significantly higher (P < 0.01) than monoculture in dark hydrogen oxidation, denitrification, nitrate denitrification, nitrous oxide denitrification, nitrite denitrification, and manganese oxidation. Plant pathogens decreased from 6.13% in monoculture to 2.46% in intercropping. Conclusion This study found that saffron-grape intercropping positively affected saffron yield. Based on the existing data, intercropping resulted in an increase in microbial communities, including some taxa previously identified as beneficial for other plants. These findings establish the foundation for the widespread application of saffron-grape intercropping and offer a promising strategy for increasing saffron yield.